Status of seroprevalence of Hepatitis B in pregnant females: a hospital-based study - Das, Rojaleen; Kumar, Shilpee (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: India has more than 37 million of HBV carriers and contributes a large proportion of the global burden. The perinatal route is the major route of the transmission. This study was conducted to estimate the seroprevalence rate of Hepatits B infection in female of reproductive age group. Since sexual route and perinatal transmission of HBV are major targets to prevent the transmission of the infection, the study focused on pregnant females attending antenatal care (ANC) clinic of the hospital. Methods: This was a retrospective observational study. The cohort enrolled for the study was pregnant females who attended the antenatal care clinic of a tertiary care hospital situated in Delhi. The blood sample was collected as a part of routine screening for HBV infection and the samples were tested for HBsAg by qualitative indirect ELISA. The study period was March to Sept 2019. Results: 7163 pregnant females were enrolled in the study and 113 were sero-positive for HBsAg. The seroprevalence of HBsAg was 1.6% (113/ 7163). The highest prevalence was found in the age group of 31-35 year (2.7%). Conclusions: As observed in the present study, the sero-prevalence rate of HBV infection in pregnant females is 1.6%, this rate amounts to nearly 4 million HBV infected women in the reproductive age and yearly putting 4 lakhs babies at risk of acquiring HBV infections by vertical transmission. The successful implementation of the National Viral Hepatitis Control Program is the need of the hour to protect every child from acquiring HBV infection.